2020
DOI: 10.7554/elife.54279
|View full text |Cite
|
Sign up to set email alerts
|

OTX2 represses sister cell fate choices in the developing retina to promote photoreceptor specification

Abstract: During vertebrate retinal development, subsets of progenitor cells generate progeny in a non-stochastic manner, suggesting that these decisions are tightly regulated. However, the gene-regulatory network components that are functionally important in these progenitor cells are largely unknown. Here we identify a functional role for the OTX2 transcription factor in this process. CRISPR/Cas9 gene editing was used to produce somatic mutations of OTX2 in the chick retina and identified similar phenotypes to those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 60 publications
5
31
1
Order By: Relevance
“…Similarly, developing oligodendrocytes expressed genes previously associates with successive stages in oligodendrocyte maturation (Goldman and Kuypers, 2015) as well a variety of other genes that now become candidates for stage-specific markers. A recent study reported on ~5,000 single cell transcriptomes from chick retinas explanted at E1.5-3 and maintained in vitro for two days (Ghinia Tegla et al, 2020). As expected from the early stage, most of their cells appear to be progenitors, which we did not find at later stages.…”
Section: Retinal Developmentcontrasting
confidence: 59%
See 1 more Smart Citation
“…Similarly, developing oligodendrocytes expressed genes previously associates with successive stages in oligodendrocyte maturation (Goldman and Kuypers, 2015) as well a variety of other genes that now become candidates for stage-specific markers. A recent study reported on ~5,000 single cell transcriptomes from chick retinas explanted at E1.5-3 and maintained in vitro for two days (Ghinia Tegla et al, 2020). As expected from the early stage, most of their cells appear to be progenitors, which we did not find at later stages.…”
Section: Retinal Developmentcontrasting
confidence: 59%
“…A recent study reported on ~5000 single-cell transcriptomes from chick retinas explanted at E1.5–3 and maintained in vitro for 2 days ( Ghinia Tegla et al, 2020 ). As expected from the early stage, most of their cells appear to be progenitors, which we did not find at later stages.…”
Section: Discussionmentioning
confidence: 99%
“…7 A). Additionally, proteomic analysis showed that the expression of Orthodenticle Homeobox 2 (OTX2) and cone-rod homeobox protein (CRX), both important proteins in the regulation of photoreceptor cell differentiation, 41 43 increased in CKO mice retinas ( Fig. 7 E).…”
Section: Resultsmentioning
confidence: 99%
“…The predicted Oc1 binding site was very conserved between ThrbCRM1 and Rxrg208 CRMs, with the predicted Otx2 binding site located very close to the predicted Oc1 site in both CRMs. Rxrg expression in cones has been shown to be regulated by Otx2 and the Onecut genes, although it was not investigated regarding whether it was direct 22,23,63 . To assess the necessity of the Otx2 and Oc1 binding sites within the Rxrg208 CRM, we cloned into Stagia3 the region corresponding to the Rxrg208 sequence with or without Oc1 and Otx2 binding sites (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
“…Since Onecut genes are not expressed in cones, and Otx2 is not expressed in HCs, yet mouse KO’s show a role for both factors in cone and HC development 23,24,26 , an early role, perhaps as pioneer factors in RPCs, is supported. As cells exit mitosis to differentiate, the roles of these two TFs may change, and may include some cross-repression 63 , as well as positive auto-regulation.…”
Section: Discussionmentioning
confidence: 99%